Evolution of Innate Immunity: Clues from Invertebrates via Fish to Mammals - Buchmann, Kurt (Frontiers in Immunology, 2014)
Host responses against invading pathogens are basic physiological reactions of all living organisms. Since appearance of the first eukaryotic cells a series of defence mechanisms have evolved in order to secure cellular integrity, homeostasis and survival of the host. Invertebrates, ranging from protozoans to metazoans, possess cellular receptors which bind to foreign elements and differentiate self from non-self. This ability is in multicellular animals associated with presence of phagocytes, bearing different names (amoebocytes, haemocytes, coelomocytes) in various groups including animal sponges, worms, cnidarians, molluscs, crustaceans, chelicerates, insects and echinoderms (sea stars and urchins). Basically these cells have a macrophage like appearance and function and the repair and/or fight functions associated with these cells are prominent even at the earliest evolutionary stage. The cells possess Pathogen Recognition Receptors (PRRs) recognizing Pathogen Associated Molecular Patterns (PAMPS) which are well conserved molecular structures expressed by various pathogens (virus, bacteria, fungi, protozoans, helminths). Scavenger receptors, Toll-like receptors (TLRs) and Nod-like receptors (NLRs) are prominent representatives within this group of host receptors. Following receptor-ligand binding signal transduction initiates a complex cascade of cellular reactions which lead to production of one or more of a wide array of effector molecules. Cytokines take part in this orchestration of responses even in lower invertebrates which eventually may result in elimination or inactivation of the intruder. The evolutionary processes associated with these reactions are discussed.